An Investigation of Market Microstructure Impacts on Event Study Returns. - Lease, Ronald C; Masulis, Ronald W; Page, John R (Journal of Finance, 1991)
The authors investigate the importance of bid-ask spread-induced biases on event date returns as exemplified by seasoned equity offerings by NYSE listed firms. They document significant negative return biases on the offering day, which explain a large portion of the negative event date returns documented in the literature. Buy-sell order flow imbalance is prominent around the offering and induces a relatively large spread bias. If order imbalances are suspected, the researcher can use returns calculated from the midpoint of the closing bid and ask quotes instead of returns calculated from closing transaction prices to avoid this return bias.